The Relationship of Gender with The Incident of Otosclerosis Based on Ear Location at The Medismart Clinic, Mataram City - I Gusti Ayu Trisna Aryani; Herpan Syafii Harahap; Hamsu Kadriyan; Azmy Mujahid, Sabila Izzatina (Jurnal Biologi Tropis, 2024)
Otosclerosis is a hearing loss disease with abnormal bone growth in the middle ear. The purpose of this study was to determine the relationship between gender and the incidence of otosclerosis based on ear location at the Medismart Mataram Clinic in 2012-2020. This cross-sectional study was conducted on 63 otosclerosis patients at the Medismart Mataram Clinic. Sampling using the total sampling technique and data were analyzed using the chi square test. The results of the statistical test showed a p-value = 0.108 in other words the p-value is greater than α = 0.05, so it can be concluded that there is no significant relationship between gender and the incidence of otosclerosis based on ear location at the Medismart Mataram Clinic. Based on the results of this study, it shows that the incidence of otosclerosis in male and female patients is not much different, the number, although women are slightly higher. So it is recommended that there is a follow-up to provide the best solution for managing otosclerosis at the Medismart Mataram Clinic.